2007
DOI: 10.1136/jcp.2006.044735
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic analysis for the detection of biomarkers in pancreatic ductal adenocarcinomas

Abstract: 30 novel potential biomarkers differentially expressed in PDAC tissues were identified. TBX4 may be a differentiation related protein; its prognostic value for PDAC deserves further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 52 publications
(38 reference statements)
1
33
0
Order By: Relevance
“…We previously observed HSP60 was found to be downregulated in PDAC compared with normal adjacent pancreas tissues in traditional 2DE analysis. IHC analyses showed that HSP60 was strongly expressed in both normal acinar cells and small ducts in normal pancreas tissues and tumor cells in all the PDAC tissues [15] . The current study extended the investigation to benign pancreatic adenoma, and revealed that HSP60 was not overexpressed in pancreatic benign lesions.…”
Section: Discussionmentioning
confidence: 99%
“…We previously observed HSP60 was found to be downregulated in PDAC compared with normal adjacent pancreas tissues in traditional 2DE analysis. IHC analyses showed that HSP60 was strongly expressed in both normal acinar cells and small ducts in normal pancreas tissues and tumor cells in all the PDAC tissues [15] . The current study extended the investigation to benign pancreatic adenoma, and revealed that HSP60 was not overexpressed in pancreatic benign lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Identification-2-D SDS-PAGE and MALDI-TOF/TOF protein identification were performed as published previously (14). Briefly, cells were scraped and harvested, then grinded with a pestle thoroughly with 100 l extraction solution containing 7 M urea, 2 M thiourea, 4% CHAPS, 60 mM dithiotreitol, 1% IPG buffer (containing carrier ampholytes, pH 3-10, Amersham Biosciences), 1 mM PMSF, 2% protease inhibitor mixture (Sigma, St Louis, MO) and 1.5% Triton X-100.…”
Section: -D Sds-page and Maldi-tof/tof Proteinmentioning
confidence: 99%
“…Similarly, Qi et al [31] utilized tissues from eight matched PDAC and noncancerous tissues and identified TBX4 to be expressed on PDAC samples. Another example is the study by Shen et al [34], who utilized frozen tissue from the National Cancer Institute Human Tissue Network and completed proteomic analysis on whole tissue homogenates from pancreatic adenocarcinoma tissues compared to normal adjacent, normal, and chronic pancreatitis tissues.…”
Section: Biological Samples For Analysismentioning
confidence: 99%
“…These studies mainly focused on the use of gel-based fractionation, usually by two-dimensional gel electrophoresis (2-DE) followed by mass spectrometry identification [31][32][33][34]. For example, Chen et al [32] analyzed tissues from three pairs of pancreatic cancer samples and compared the samples to adjacent noncan cerous tissues resected from the same patient, and found that S100A11 and galectin-3 were overexpressed in pancreatic cancer.…”
Section: Biological Samples For Analysismentioning
confidence: 99%